2001
DOI: 10.1128/jvi.75.1.52-60.2001
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T Cells and Gamma Interferon in the Long-Term Control of Persistent Friend Retrovirus Infection

Abstract: We have used the Friend virus model to determine the basic mechanisms by which the immune system can control persistent retroviral infections. Previously we showed that CD4 ؉ T cells play an essential role in keeping persistent retrovirus in check. The present in vitro experiments with a Friend virus-specific CD4 ؉ T-cell clone revealed that these cells produce gamma interferon (IFN-␥), which acts with two distinct mechanisms of antiviral activity. First, IFN-␥ had a direct inhibitory effect on virus productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…ϩ T-cell clones were shown to possess cytolytic activity and to inhibit the production of virus in vitro (19). The clones that we isolated secreted IFN-␥ and possessed cytolytic activity on specific stimulation, consistent with the Th1-type clones identified in murine studies.…”
Section: Vol 75 2001supporting
confidence: 54%
“…ϩ T-cell clones were shown to possess cytolytic activity and to inhibit the production of virus in vitro (19). The clones that we isolated secreted IFN-␥ and possessed cytolytic activity on specific stimulation, consistent with the Th1-type clones identified in murine studies.…”
Section: Vol 75 2001supporting
confidence: 54%
“…Like the endogenous population of tetramer-positive CD8 ϩ T cells, adoptively transferred CD8 ϩ T cells that were suppressed before anti-CD137 therapy also up-regulated granzyme B. However, neither type of cell developed high IFN-␥ production as a result of anti-CD137 therapy, a cytokine known to be important in control of chronic FV infections (52,53). Although there was a slight but significant reduction in chronic virus levels in anti-CD137-treated mice without T cell transfers at the 2-wk time point ( p ϭ 0.0389), by 4 wk virus levels were back to normal (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the Friend virus (FV) model of retroviral infection in mice have shown an association between T-cell production of IFN-␥ in vitro and recovery from acute infection in vivo (45). In addition, IFN-␥ has been shown to play an important role in controlling persistent FV infection (30). However, we still do not understand the role of IFN-␥ in virus spread and pathogenesis during the course of FV infection.…”
mentioning
confidence: 90%